2020
DOI: 10.5603/cj.a2018.0144
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for early mortality and arrhythmic events in patients with cardiac resynchronization therapy with defibrillator: A two center cohort study

Abstract: Background: Guidelines of heart failure therapy include cardiac resynchronization as standard of care in patients with severely depressed left ventricular function and wide QRS complex. It has been shown that patients benefit regarding mortality and morbidity. However, early mortality precludes longterm benefits from the device. The aim of the study was to identify predictors for early occurrence of both death and first-ever implantable cardioverter-defibrillator (ICD) therapy using a large combined database o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Baseline medical therapy in major registries and cohort studies of CRT and ICD (n 5 19) is presented in Figure 3. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] CRT studies reported ACEI/ARB and betablocker baseline use in 78% (52%-100%) and 80% (70%-87%). Uptake was similar in ICD studies, 78% (59%-99%) and 85% (53%-97%), respectively.…”
Section: Baseline Medical Therapy In Registries and Cohort Studiesmentioning
confidence: 99%
“…Baseline medical therapy in major registries and cohort studies of CRT and ICD (n 5 19) is presented in Figure 3. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] CRT studies reported ACEI/ARB and betablocker baseline use in 78% (52%-100%) and 80% (70%-87%). Uptake was similar in ICD studies, 78% (59%-99%) and 85% (53%-97%), respectively.…”
Section: Baseline Medical Therapy In Registries and Cohort Studiesmentioning
confidence: 99%